Hierarchical electrode design of highly efficient and stable unitized regenerative fuel cells (URFCs) for long-term energy storage. Issue 12 (5th November 2020) - Peng, Xiong; Taie, Zachary; Liu, Jiangjin; Zhang, Yaqian; Peng, Xinxing; Regmi, Yagya N.; Fornaciari, Julie C.; Capuano, Christopher; Binny, Dustin; Kariuki, Nancy N.; Myers, Deborah J.; Scott, Mary C.; et al.
Abstract : The unitized regenerative fuel cell (URFC) is a promising electrochemical device for intermittent renewable energy storage in chemical bonds. Abstract : The unitized regenerative fuel cell (URFC) is a promising electrochemical device for intermittent renewable energy storage in chemical bonds. However, widespread application has been hindered due to low round-trip efficiencies (RTEs) and disappointing durability, in particular at high rates. Here, we break through that barrier by demonstrating highly efficient, flexible, and stable URFCs via hierarchical design of the multiscale catalyst-layer structures. A more porous and less tortuous Pt and Ir catalyst layer is realized using a doctor blade fabrication method that significantly improves URFC performance. We demonstrate RTEs of 56% and 53% under constant-electrode and constant-gas mode, respectively, while operating at 1000 mA cm −2, and significantly, a RTE of 45% at 2000 mA cm −2, achievements that were previously viewed as unfeasible under the onerous demands of URFC operation. At the same time we demonstrate URFCs under both constant-electrode and constant-gas mode operated continuously for over 500 h with negligible degradation. These results demonstrate the viability of applying URFCs for long-term energy storage at previously unattainable efficiencies and cast new light on electrode design and optimization of URFCs.